Pharmacological and Surgical Treatment for Trigeminal Neuralgia a Review of the Literature (International Journal of Medical and Surgical Sciences, 2014)
Trigeminal neuralgia is the most common orofacial pain, with incidence levels that increase every year. Characterized by paroxysmal attacks of pain, brief, lancinating, stabbing, is considered one of the most painful conditions affecting patients. Drug therapy has been the gold standard for the management and control of this neuropathy, on the contrary, recent studies find wide drug resistance with history of neuralgia for many years, causing recurrence of the picture. That is why there is a need to establish a proper surgical planning, among which stands vascular decompression and percutaneous micro harmful methods such as retrogasserianas rhizotomies, chemical methods, such as injection of alcohol or glycerol in the oval hole, mental foramen, as an alternative to medical-pharmacological treatment, however, not all procedures reviewed in the literature indicate a continued success rate and further, the various adverse effects involving the implementation of each treatment should be considered.
Keywords: Trigeminal nerve; Trigeminal neuralgia; Carbamazepine; Rhyzotomy; Cryosurgery